2015
DOI: 10.3389/feart.2015.00075
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Seedlings of a Shade-Tolerant Tropical Tree Species after Moderate Addition of N and P

Abstract: Nitrogen deposition to tropical forests is predicted to increase in future in many regions due to agricultural intensification. We conducted a seedling transplantation experiment in a tropical premontane forest in Ecuador with a locally abundant late-successional tree species (Pouteria torta, Sapotaceae) aimed at detecting species-specific responses to moderate N and P addition and to understand how increasing nutrient availability will affect regeneration. From locally collected seeds, 320 seedlings were prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…For seedlings of Pouteria torta that were transplanted for one year to our study plots at 1000 m asl (2011–2012), Cárate‐Tandalla et al . () reported an increase in herbivory in the P‐ and N+P‐treated plots. By contrast, our results show only slightly (but not significantly) higher leaf area loss in this species in the same treatments.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…For seedlings of Pouteria torta that were transplanted for one year to our study plots at 1000 m asl (2011–2012), Cárate‐Tandalla et al . () reported an increase in herbivory in the P‐ and N+P‐treated plots. By contrast, our results show only slightly (but not significantly) higher leaf area loss in this species in the same treatments.…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, Cárate‐Tandalla et al . () observed increased diameter growth for Pouteria torta seedlings after N or P addition but no change in foliar concentrations of these elements. However, some studies have reported luxury consumption of P following P additions in tropical plant species, which were not accompanied by observed functional responses (Ostertag , Mayor et al .…”
mentioning
confidence: 83%
See 3 more Smart Citations